Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine which reflection will transform the endpoints of the line segment from [tex]$(-4, -6)$[/tex] and [tex]$(-6, 4)$[/tex] to [tex]$(4, 6)$[/tex] and [tex]$(6, 4)$[/tex], let's analyze each reflection option step-by-step.
Step 1: Reflection across the [tex]\(x\)[/tex]-axis
The reflection of each point [tex]\((x, y)\)[/tex] across the [tex]\(x\)[/tex]-axis is [tex]\((x, -y)\)[/tex].
- For point [tex]\((-4, -6)\)[/tex]:
[tex]\[ (x, y) \rightarrow (x, -y) \Rightarrow (-4, -6) \rightarrow (-4, 6) \][/tex]
- For point [tex]\((-6, 4)\)[/tex]:
[tex]\[ (x, y) \rightarrow (x, -y) \Rightarrow (-6, 4) \rightarrow (-6, -4) \][/tex]
The resulting points are [tex]\((-4, 6)\)[/tex] and [tex]\((-6, -4)\)[/tex], which do not match the target points [tex]\((4, 6)\)[/tex] and [tex]\((6, 4)\)[/tex].
Step 2: Reflection across the [tex]\(y\)[/tex]-axis
The reflection of each point [tex]\((x, y)\)[/tex] across the [tex]\(y\)[/tex]-axis is [tex]\((-x, y)\)[/tex].
- For point [tex]\((-4, -6)\)[/tex]:
[tex]\[ (x, y) \rightarrow (-x, y) \Rightarrow (-4, -6) \rightarrow (4, -6) \][/tex]
- For point [tex]\((-6, 4)\)[/tex]:
[tex]\[ (x, y) \rightarrow (-x, y) \Rightarrow (-6, 4) \rightarrow (6, 4) \][/tex]
The resulting points are [tex]\((4, -6)\)[/tex] and [tex]\((6, 4)\)[/tex], which do not match the target points [tex]\((4, 6)\)[/tex] and [tex]\((6, 4)\)[/tex].
Step 3: Reflection across the line [tex]\(y = x\)[/tex]
The reflection of each point [tex]\((x, y)\)[/tex] across the line [tex]\(y = x\)[/tex] is [tex]\((y, x)\)[/tex].
- For point [tex]\((-4, -6)\)[/tex]:
[tex]\[ (x, y) \rightarrow (y, x) \Rightarrow (-4, -6) \rightarrow (-6, -4) \][/tex]
- For point [tex]\((-6, 4)\)[/tex]:
[tex]\[ (x, y) \rightarrow (y, x) \Rightarrow (-6, 4) \rightarrow (4, -6) \][/tex]
The resulting points are [tex]\((-6, -4)\)[/tex] and [tex]\((4, -6)\)[/tex], which do not match the target points [tex]\((4, 6)\)[/tex] and [tex]\((6, 4)\)[/tex].
Step 4: Reflection across the line [tex]\(y = -x\)[/tex]
The reflection of each point [tex]\((x, y)\)[/tex] across the line [tex]\(y = -x\)[/tex] is [tex]\((-y, -x)\)[/tex].
- For point [tex]\((-4, -6)\)[/tex]:
[tex]\[ (x, y) \rightarrow (-y, -x) \Rightarrow (-4, -6) \rightarrow (6, 4) \][/tex]
- For point [tex]\((-6, 4)\)[/tex]:
[tex]\[ (x, y) \rightarrow (-y, -x) \Rightarrow (-6, 4) \rightarrow (-4, -6) \][/tex]
The resulting points are [tex]\((6, 4)\)[/tex] and [tex]\((-4, -6)\)[/tex], which also do not match the target points [tex]\((4, 6)\)[/tex] and [tex]\((6, 4)\)[/tex].
Given the evaluation of each type of reflection, we can conclude that none of the provided reflections result in endpoints at [tex]\((4, 6)\)[/tex] and [tex]\((6, 4)\)[/tex]. Therefore, the answer is:
No valid reflection found.
Step 1: Reflection across the [tex]\(x\)[/tex]-axis
The reflection of each point [tex]\((x, y)\)[/tex] across the [tex]\(x\)[/tex]-axis is [tex]\((x, -y)\)[/tex].
- For point [tex]\((-4, -6)\)[/tex]:
[tex]\[ (x, y) \rightarrow (x, -y) \Rightarrow (-4, -6) \rightarrow (-4, 6) \][/tex]
- For point [tex]\((-6, 4)\)[/tex]:
[tex]\[ (x, y) \rightarrow (x, -y) \Rightarrow (-6, 4) \rightarrow (-6, -4) \][/tex]
The resulting points are [tex]\((-4, 6)\)[/tex] and [tex]\((-6, -4)\)[/tex], which do not match the target points [tex]\((4, 6)\)[/tex] and [tex]\((6, 4)\)[/tex].
Step 2: Reflection across the [tex]\(y\)[/tex]-axis
The reflection of each point [tex]\((x, y)\)[/tex] across the [tex]\(y\)[/tex]-axis is [tex]\((-x, y)\)[/tex].
- For point [tex]\((-4, -6)\)[/tex]:
[tex]\[ (x, y) \rightarrow (-x, y) \Rightarrow (-4, -6) \rightarrow (4, -6) \][/tex]
- For point [tex]\((-6, 4)\)[/tex]:
[tex]\[ (x, y) \rightarrow (-x, y) \Rightarrow (-6, 4) \rightarrow (6, 4) \][/tex]
The resulting points are [tex]\((4, -6)\)[/tex] and [tex]\((6, 4)\)[/tex], which do not match the target points [tex]\((4, 6)\)[/tex] and [tex]\((6, 4)\)[/tex].
Step 3: Reflection across the line [tex]\(y = x\)[/tex]
The reflection of each point [tex]\((x, y)\)[/tex] across the line [tex]\(y = x\)[/tex] is [tex]\((y, x)\)[/tex].
- For point [tex]\((-4, -6)\)[/tex]:
[tex]\[ (x, y) \rightarrow (y, x) \Rightarrow (-4, -6) \rightarrow (-6, -4) \][/tex]
- For point [tex]\((-6, 4)\)[/tex]:
[tex]\[ (x, y) \rightarrow (y, x) \Rightarrow (-6, 4) \rightarrow (4, -6) \][/tex]
The resulting points are [tex]\((-6, -4)\)[/tex] and [tex]\((4, -6)\)[/tex], which do not match the target points [tex]\((4, 6)\)[/tex] and [tex]\((6, 4)\)[/tex].
Step 4: Reflection across the line [tex]\(y = -x\)[/tex]
The reflection of each point [tex]\((x, y)\)[/tex] across the line [tex]\(y = -x\)[/tex] is [tex]\((-y, -x)\)[/tex].
- For point [tex]\((-4, -6)\)[/tex]:
[tex]\[ (x, y) \rightarrow (-y, -x) \Rightarrow (-4, -6) \rightarrow (6, 4) \][/tex]
- For point [tex]\((-6, 4)\)[/tex]:
[tex]\[ (x, y) \rightarrow (-y, -x) \Rightarrow (-6, 4) \rightarrow (-4, -6) \][/tex]
The resulting points are [tex]\((6, 4)\)[/tex] and [tex]\((-4, -6)\)[/tex], which also do not match the target points [tex]\((4, 6)\)[/tex] and [tex]\((6, 4)\)[/tex].
Given the evaluation of each type of reflection, we can conclude that none of the provided reflections result in endpoints at [tex]\((4, 6)\)[/tex] and [tex]\((6, 4)\)[/tex]. Therefore, the answer is:
No valid reflection found.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.